The night swimmer [large type] - Bondurant, Matt, 1971- (Thorndike Press large print basic series., 2012)
When Vermonters Fred and Elly Bulkington win a pub in a contest, they travel to a small town on the southern coast of Ireland and encounter a wild, strange land - and the native resistance to strangers. As Fred immerses himself in the life of a pub-owner, Elly takes the ferry to a nearby island where she devotes herself to open-water swimming, pushing herself to the limit, and crossing unseen boundaries that drive her into the heart of the island's troubles.